2014
DOI: 10.2533/chimia.2014.799
|View full text |Cite
|
Sign up to set email alerts
|

Towards Mechanistic Understanding of Mercury Availability and Toxicity to Aquatic Primary Producers

Abstract: The present article reviews current knowledge and recent progress on the bioavailability and toxicity of mercury to aquatic primary producers. Mercury is a ubiquitous toxic trace element of global concern. At the base of the food web, primary producers are central for mercury incorporation into the food web. Here, the emphasis is on key, but still poorly understood, processes governing the interactions between mercury species and phytoplankton, and macrophytes, two representatives of primary producers. Mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Bravo et al () suggested that in eutrophic lakes receiving low inputs of terrigenous OM, sediment Hg concentrations are determined by atmospheric inputs. Besides dissolved Hg II , lipophilic Hg compounds such as uncharged HgCl 2 and CH 3 HgCl complexes are important for the uptake by algae (Mason et al ; Dranguet et al ), but binding to terrestrial DOM limits the uptake of both metals (e.g., (Brooks et al ; Schartup et al b ). Enhanced photo‐oxidation of DOM‐Hg under higher TSI might enhance Hg II uptake by algae, in a similar way as found for Cu (Moffett et al ; Sander et al ; Shank et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bravo et al () suggested that in eutrophic lakes receiving low inputs of terrigenous OM, sediment Hg concentrations are determined by atmospheric inputs. Besides dissolved Hg II , lipophilic Hg compounds such as uncharged HgCl 2 and CH 3 HgCl complexes are important for the uptake by algae (Mason et al ; Dranguet et al ), but binding to terrestrial DOM limits the uptake of both metals (e.g., (Brooks et al ; Schartup et al b ). Enhanced photo‐oxidation of DOM‐Hg under higher TSI might enhance Hg II uptake by algae, in a similar way as found for Cu (Moffett et al ; Sander et al ; Shank et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidized dissolved Hg (Hg II ‐species such as HgCl 2 ) and methylmercury (CH 3 HgX, (MeHg)) are the dominant species taken up. Lipophilic CH 3 HgCl has a higher bioaccumulation factor than other Hg II ‐species, whereas DOM‐bound Hg appears to decrease uptake by algae (Dranguet et al ; Le Faucheur et al ; Schartup et al b ). Direct uptake of dissolved or gaseous elemental mercury (GEM) by phytoplankton seems to be of minor importance as no detectable accumulation of Hg could be observed when GEM was used in bioaccumulation experiments (Le Faucheur et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury (Hg) contamination of freshwaters arises from the deposition of atmospheric Hg (dry settling or rainfall), polluted soils runoffs, industrial effluents, gold-mining and reemission from historical contaminated systems ( [1,2]). It subsequently settles in the sediment of lakes, rivers or bays where it is transformed into methylmercury (MeHg), absorbed by primary producers, transferred to primary and secondary consumers, and accumulates especially in long-lived predatory species, e.g., shark and swordfish.…”
Section: Introductionmentioning
confidence: 99%
“…Typical environmental concentrations measured in rivers and lakes range between 0.003 and 30 nM THg ( [5]). Both IHg and MeHg are mainly bound to dissolved organic matter (DOM) ( [1,6,7]) in particular to thiol (RSH) groups. For the fraction of Hg not bound with DOM, water chemistry (e.g., pH and chloride concentration) controls its distribution among different dissolved chemical species and complexes ( [8,9]).…”
Section: Introductionmentioning
confidence: 99%